Melanoma to papillary thyroid carcinoma: A case of tumor-to-tumor metastasis to the head and neck and a re-evaluation of diagnostic criteria - Dennis E. Curry; Matthew H. Rigby; Martin Bullock (Elsevier, 2020)
Tumor-to-tumor metastasis is a rare clinical phenomenon variably defined within the literature. Breast and lung cancers are the most common sites of origin, while renal cell carcinoma is the most common site of receipt. Cases wherein the recipient malignancy is of thyroid origin are exceedingly rare. We report on a case of melanoma metastatic to a papillary thyroid carcinoma (PTC). We review related literature and re-evaluate relevant clinical definitions.